Immunogenicity and safety of seasonal influenza vaccines in children under 3 years of age. (31st December 2023) - Aoun, Tia; Borrow, Ray; Arkwright, Peter D.
ABSTRACT: Introduction: Despite children aged 6–35 months developing more severe influenza infections, not all countries include influenza vaccines in their national immunization programs. Areas covered: This literature review examines the efficacy, immunogenicity, and safety of seasonal trivalent influenza vaccines (TIVs) and quadrivalent influenzae vaccines (QIVs) in children 6–35 months old to determine if greater valency promotes greater protection while maintaining a similar safety profile. Expert opinion: TIVs and QIVs are safe for children under 3 years old. TIVs and QIVs provided good seroprotection, and immunogenicity (GMT, SCR, and SPR) meeting recommended levels set by CHMP (European) and CBER (USA). However, as QIVs carry two influenza B strains and TIVs only one, QIVs has an overall higher seroprotection against particularly influenza B. Vaccines containing adjuncts had better immunogenicity, particularly after the first dose. Seroprotection of all vaccines lasted 12 months. Increasing the dosage from 0.25 mL to 0.5 mL did not cause more systemic or local side-effects. Further comparisons of efficacy, and wider promotion of influenza vaccines in general are required in preschool children.